Improving child health service interventions through a Theory of Change: A scoping review - Jones, B; Paterson, A; English, M; Nagraj, S (Frontiers Media, 2023)
Background: The objective of this scoping review was to map how child health service interventions develop, utilise, and refine theories of change. A Theory of Change (ToC) is a tool for designing, implementing, and evaluating interventions that is being increasingly used by child health practitioners who are aiming to enact change in health services.